Analisis Kebijakan Implementasi Pembelajaran Berbasis Proyek Melalui Program P5 pada Kurikulum Merdeka di SMK Pembangunan Bandung Barat - Hafidin Nurhadi; Ani Fatimah Zahra Saifi; Erik Jaenudin; Supiana Supiana; Qiqi Yuliati Zakiyah (Journal on Education, 2024)
The Pancasila Student Profile Strengthening Project (P5) Program Policy is a manifestation of Project-Based Learning in the Independent Curriculum. The P5 program is based on the need to prepare Indonesia's young generation to face increasingly complex global challenges, as well as the importance of strengthening character based on Pancasila values. A good policy must be analyzed first by taking the following procedures (steps): 1) Problem Identification, 2) Development of Assessment Criteria, 3) Identification of Policy Alternatives, 4) Evaluation of Policy Alternatives, 5) Policy Recommendations, 6) Policy Implementation, 7) Policy Evaluation and Supervision. This study aims to analyze the policy steps for the implementation of project-based learning through the P5 program at SMK Pembangunan Bandung Barat. This research uses a qualitative approach with literature review and case study methods. Some of the problems that arise in the implementation of project-based learning through the P5 program at SMK Pembangunan Bandung Barat are: 1) Limited understanding of teachers about PBL and the concept of P5, 2) Limited resources and facilities, 3) Limited learning time, 4) Lack of student involvement, 5) Less comprehensive assessment, 6) Lack of collaboration with the community or the surrounding environment, 7) Challenges in group management, 8) Limitations in teacher training, 9) Administrative obstacles and school policies. Policy recommendations in the implementation of project-based learning through the P5 program at SMK Pembangunan Bandung Barat are: 1) Prioritize continuous training and mentoring for teachers, 2) Develop partnerships with external institutions, 3) Integrate P5 in the existing curriculum, 4) Simplify and standardize assessment instruments, 5) Apply P5 scale adjustments based on school resources, 6) Utilize technology to support P5.